Teoria dos sistemas: a comunicação e a linguagem como abertura causal para garantia da clausura operacional dos sistemas sociais - Lira, Cláudio Rogério Sousa (2015)
The proposed study will approach Theory of Systems and the importance of communication and language for the operational closure of social systems. Therefore, it will be made a literature review on Systemic Theory from its main international and national authors, enabling a (re)discussion about the role of communication and language in the relationship between systems and environment. What will be seen among the developed lines of this article is that there is no society without communication. Communication takes place through language. Thus, we intend to sustain that communication depends on the language, in other words, there is no communication without language. Therefore, we can afirm that language marks the difference in communication between system and environment, and this function represents the stability of the system in the self-organizational level and in the (re)production.